The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jof7070531
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizae Mitigate Aluminum Toxicity and Regulate Proline Metabolism in Plants Grown in Acidic Soil

Abstract: Arbuscular mycorrhizal fungi (AMF) can promote plant growth and induce stress tolerance. Proline is reported to accumulate in mycorrhizal plants under stressful conditions, such as aluminum (Al) stress. However, the detailed changes induced in proline metabolism under AMF–plant symbiosis has not been studied. Accordingly, this work aimed to study how Al-stressed grass (barley) and legume (lotus) species respond to AMF inoculation at growth and biochemical levels. The associated changes in Al uptake and accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Previously, Hussain et al [11] have reported that AMF coating on seeds enhanced root colonization in maize plants. AMF not only improves colonization and protects plants under high-temperature stress as shown in the present study but also mitigated the impact of Al toxicity in lotus and barley plants by accumulating Al in roots and ultimately protecting the plants from metal stress as well [14]. Root colonization helped in the upregulation of photosynthetic rate in AMF and AMF + HT plants.…”
Section: Root Colonization and Spore Densitysupporting
confidence: 69%
See 2 more Smart Citations
“…Previously, Hussain et al [11] have reported that AMF coating on seeds enhanced root colonization in maize plants. AMF not only improves colonization and protects plants under high-temperature stress as shown in the present study but also mitigated the impact of Al toxicity in lotus and barley plants by accumulating Al in roots and ultimately protecting the plants from metal stress as well [14]. Root colonization helped in the upregulation of photosynthetic rate in AMF and AMF + HT plants.…”
Section: Root Colonization and Spore Densitysupporting
confidence: 69%
“…Various studies have reported that AMF improved stress mitigation and tolerance in plants [11,13,14,23,42,43]. AMF increases plant growth by improving nutrition acquisition, root architecture, and increasing antioxidant activity, as well as stress tolerance [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One the most important characteristics of this AM symbiosis is to help the host absorb nutrients and water that cannot be reached by the root, to enhance the resistance of the host plant to abiotic stress [ 11 , 12 ]. The AM symbiosis between AM fungi and host plants enhances the resistance of host plants to drought, salt stress, high temperature, nutrient stress, aluminum toxicity, and waterlogging stress by affecting their antioxidant enzyme defense systems [ 13 , 14 , 15 , 16 ]. Zhang et al [ 17 ] observed an induced expression of superoxide dismutase ( SOD ) and catalase ( CAT ) genes in roots of trifoliate orange ( Poncirus trifoliata L.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids were determined from 200 mg of sprouts combined with 1 mL of 80% (v/v) aqueous ethanol [24]. For accurate evaluation and correction of varied mass spectrometry reactions, norvaline was employed as an internal standard.…”
Section: Amino Acid Determinationmentioning
confidence: 99%